Endostatin in pathogenesis of psoriatic process - Zalewska, Anna; Sysa-Jędrzejowska, Anna; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Psoriasis is characterized by enhanced angiogenesis, which is reflected by increased levels, both systemically and lesionally, of pro-angiogenic factors and decreased levels of inhibitors of this process. On the other hand, endostatin is one of the naturally occurring inhibitors of neovascularization. The aim of the study was to evaluate endostatin plasma levels in different activity phases in psoriasis vulgaris patients. The study consisted of 99 in-patients with active psoriasis treated with four different methods: anthralin, Ingram method, Goeckerman method and methorexate. The control group comprised 40 healthy volunteers. Severity of the disease was evaluated by PASI score. Blood samples were collected before treatment and 3 weeks thereafter. Plasma levels of endostatin were measured by ELISA. Endostatin levels were significantly elevated in psoriatic patients irrespective of the treatment employed in comparison to the control group (p<0.001). The levels of endostatin were significantly higher after treatment when compared to baseline results, independently from the applied therapy (p<0.001). The obtained results demonstrate some disturbances in endostatin levels in psoriatic patients.